2022
DOI: 10.1007/s00210-022-02279-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular protection by DPP-4 inhibitors in preclinical studies: an updated review of molecular mechanisms

Abstract: Dipeptidyl peptidase 4 (DPP4) inhibitors are a class of antidiabetic medications that cause glucose-dependent increase in incretins in diabetic patients. One of the two incretins, glucagon-like peptide-1 (GLP-1), beside its insulinotropic activity, has been studied for extra pancreatic effects. Most of DPP4 inhibitors (DPP4i) have been investigated in in vivo and in vitro models of diabetic and nondiabetic cardiovascular diseases including heart failure, hypertension, myocardial ischemia or infarction, atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…In a review by Zakaria et al, it was found that DPP-4 inhibitors had beneficial effects on the cardiovascular system by modulating the levels of vasoactive cardio-protectant peptides like B-type natriuretic peptide (BNP), stromal cell-derived factor 1α (SDF-1α) and substance P [ 53 ]. They also exert positive effects on the cardiovascular system through mechanisms like reducing hyperglycemia, reducing oxidative damage and inflammation, promoting tissue repair, and protecting the endothelial function, leading to better perfusion of the myocardium [ 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a review by Zakaria et al, it was found that DPP-4 inhibitors had beneficial effects on the cardiovascular system by modulating the levels of vasoactive cardio-protectant peptides like B-type natriuretic peptide (BNP), stromal cell-derived factor 1α (SDF-1α) and substance P [ 53 ]. They also exert positive effects on the cardiovascular system through mechanisms like reducing hyperglycemia, reducing oxidative damage and inflammation, promoting tissue repair, and protecting the endothelial function, leading to better perfusion of the myocardium [ 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, there is a disconnect between animal studies of DPP‐4 inhibitors and the aforementioned clinical studies on the effects of DPP‐4 inhibitors in patients with CAD. Mouse studies have shown increased angiogenesis, decreased ischemic reperfusion injury, and decreased coronary atherosclerosis with DPP‐4 inhibitors (Abbas et al., 2018 ; Al‐Awar et al., 2018 ; Bradic et al., 2021 ; Fan et al., 2020 ; Khodeer et al., 2019 ; Zakaria et al., 2022 ). Other mouse studies modeling heart failure have shown increased cardiac function and decreased diastolic dysfunction with DPP‐4 inhibitors (Beraldo et al., 2019 ; Esposito et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%